Precipitation and temperature characteristics of forested watershed in Central Arizona - Campbell, Ralph E.; Ryan, Michael G. (USDA Forest Service general technical report, 1982)
Precipitation and temperature characteristics of the Utah and alligator juniper woodlands and ponderosa pine forest types, n the Beaver Creek experimental watersheds, are described using 23 years of record. Mean annual precipitation ranges from 17.6 inches in the Utah juniper type are 7, 400 feet elevation. Average precipitation is greater for winter storms than for summer stoems. Precipitation intensity exceeding 3 inches per hour for 30 minutes' duration may be expected to occur on the average at 25-year intervals on the three vegetation types. Temperatures are closely correlated with elevation. The climatic patterns, both precipitation and temperature, are quite representative pf similar vegetation types am fit into a continuum within Arizona and New Mexico.